Development of diode temperature sensors with operating range up to 750 K - Krasnov, Vasily; Yerochin, Sergey; Demenskyi, Oleksii; Krapyvko, Gennadii (Eastern-European Journal of Enterprise Technologies, 2018)
The problem of expansion of the range of functioning of diode thermosensors in the region of high temperatures is considered and some of the results of the author’s research in this area are given. To solve this problem, it is proposed to use diode structures based on wide bandgap semiconductor compounds in the III-V system. The technological method of producing prototypes of high-temperature diode temperature sensors based on GaP is developed. The presented method allows manufacturing samples of diode temperature sensors, the high-temperature limit of which exceeds the limit of functioning of commercial silicon diode temperature sensors by about 200–300 K. The experimental methods of obtaining epitaxial structures of solid solutions of AlGaAs and fabricating diode temperature sensors based on them are developed. It is shown that the approach chosen in this work allows extending the thermometric characteristics of such diodes in the high-temperature region by approximately 150–250 K. The paper presents the methodology for forming InGaN device structures and production of prototype high-temperature diode temperature sensors based on them. This technique with revisions can be used for the manufacture of diode temperature sensors and other devices for high-temperature applications, the entire range of solid solutions in the InN-GaN system. The parameters and characteristics of the obtained diode temperature sensors are investigated. The results of the research can be used by specialists in the field of electronics and optoelectronics in the development and production of semiconductor devices.